MANAJEMEN PENGEMBANGAN PROFESIONAL SEBAGAI UPAYA PENINGKATAN KINERJA GURU DI SMPN 1 CIMANGGUNG KABUPATEN SUMEDANG - Meliyanti; Wasliman, Eva Dianawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study analyzes teacher professional development management as an effort to enhance teacher performance at SMP Negeri 1 Cimanggung, Sumedang Regency. The focus of the study consists of four main aspects of POAC-based management: planning, organizing, implementing, and evaluating. A qualitative approach using case study methods was used to gain an in-depth understanding. Data were collected through interviews, observations, and document analysis, then analyzed using data reduction, presentation, and conclusion drawing. The results of the study indicate that planning based on needs analysis, Education Reports, and competency gaps produces targeted programs. Organization involves effective task distribution, optimization of the roles of the vice principal, School Learning Community (Kombel) coordinator, and collaboration among teachers, although external partnerships can still be improved. Implementation includes training, workshops, clinical supervision, mentoring, and Learning Community activities that improve teachers' pedagogical and professional competencies. Evaluation is conducted through continuous monitoring, evaluation meetings, follow-up analysis, and supervision instruments. The implementation of this management runs in an integrated and continuous POAC cycle, resulting in improved teacher performance, learning quality, and a collaborative work culture. The findings confirm the strategic role of the principal as an education manager and provide a model that can be used as a reference for teacher professional development in other schools.